The Role of Spiritual Intelligence And Self-Efficacy In Enhancing Elementary School Students' Academic Achievement: A Systematic Literature Review - Munandar, Arif; Supriyatna, Encep; Rahayu, Ida (International Conference on Elementary Education, 2025)
Modern education often overemphasizes cognitive achievement, neglecting internal student factors crucial for holistic learning success. This study aims to deeply synthesize and analyze the synergistic role of spiritual intelligence and self-efficacy in enhancing the academic achievement of elementary school students. Using a Systematic Literature Review (SLR) approach, relevant articlesfrom databases such as Google Scholar and Garuda were identified and analyzed through a rigorous selection process to map the existing evidence. The synthesis results reveal three main findings: (1) Self-efficacy consistently proves to be a strong predictor of academic achievement, functioning as the "I can" belief that motivates students to strive and persist. (2) Spiritual intelligence positively influences achievement by providing the foundational "why" students should learn, fostering meaning, purpose,and intrinsic motivation. (3) A significant reciprocal relationship exists, where spiritual intelligence can be the foundation that strengthens the development of resilient self-efficacy. It is concluded that the combination of spiritual intelligence and self-efficacy creates an optimal internal psychological ecosystem for academic achievement. The implication of this finding is the urgent need for a shift towards a more holistic pedagogy in elementary schools, one that not only hones intellectual aspects but also consciously cultivates students' spiritual dimensions and self-beliefs to create a complete learning system